Bathybembix bairdii (Mollusca: Gastropoda: Calliotropidae) as a potential fishery resource off western Mexico (Revista de Biología Marina y Oceanografía, 2018)
Bathybembix bairdii, the Baird's top shell, is reported for the first time from off the Baja California Peninsula west coast and the southwestern coast of Mexico, at depths of 710-2,093 m. Environmental conditions measured near bottom were: 2.10 to 5.81 °C, 34.40 to 34.63 (salinity), and